Mempersiapkan Usia Lanjut yang Bebas Nyeri Lutut di Kelurahan Pandean Lamper, Kecamatan Gayam Sari - Christiana, Metta; Muhaimin, Ahmad; Cahyo, Andi Nur; Maulana, Charis (STIE Pelita Nusantara, 2022)
Translator The problem in Pandean Lamper Semarang Village is that as many as 30% of the elderly and elderly people experience knee pain that interferes with daily activities. Most of them (90%) do not know how to maintain knee health. The purpose of this activity is to provide knowledge and training for the elderly and elderly on how to maintain knee health. The method of implementing the activities is by giving lectures, questions and answers and training. The result of the activity is that participants' knowledge about how to maintain knee health increases, the post test results show an increase in knowledge, namely almost 100% of participants understand how to maintain knee health. Participants are also able to perform movements for the prevention of knee pain, although not yet perfect. The conclusion of this activity is that the knowledge and ability of pre-elderly and elderly citizens in maintaining knee health increases.Keywords: Elderly, knee pain free